Eksistensi Peraturan Daerah Kota Mataram Nomor 10 Tahun 2015 tentang Pedagang Kaki Lima dalam Meningkatkan Potensi Pajak dan Retribusi Daerah (Mimbar Keadilan, 2023)
The purpose of this study is to determine the existence of Mataram City Regional Regulation No. 10/2015 concerning Street Vendors (PKL) in increasing the potential for regional taxes and fees on the PKL sector in the regional government of Mataram city and the impact after the Street Vendors Sector (PKL) was designated as a Potential Regional Tax and Retribution in the Regional Government of Mataram City. The research method used in this research is Normative Law research method. While the technique of collecting legal materials in this study is to use library research. The results of this study are the existence of Mataram City Regional Regulation No. 10/2015 concerning Street Vendors cannot be used as a legal basis as a legal umbrella in determining the Street Vendors (PKL) sector as a potential Regional Tax and Retribution in the City of Mataram, because materially there is no article or paragraph material in it which mentions and discusses matters meant. This legal basis is absolutely necessary as a basis for street vendors to become potential regional taxes and levies for the city of Mataram. There are three impacts that arise after the street vendors sector is designated as a potential Regional Tax and Retribution. The first is against street vendors (PKL). Next to Non-PKL Traders. Then to the Government and Society.